Implementasi Sensor DHT22 dan SHT31 di Ruang Komputer dan Perancangan Gedung Laboratorium Elektronika Polnep untuk Pengendalian AC (Air Conditioner) Otomatis - Muhammad Al Khawarizmi; Satriyo; Mohd. Ilyas Hadikusuma; Teguh M. Fiqri (JOURNAL SAINS STUDENT RESEARCH, 2026)
Inefficient use of Air Conditioners (AC) in computer rooms leads to energy waste and potential device damage due to uncontrolled temperature. This study designs and implements an automatic AC control system based on an ESP32 microcontroller equipped with DHT22 and SHT31 temperature sensors in the Computer and Design Room of the Electronics Laboratory Building at Politeknik Negeri Pontianak. The system uses an IR transmitter module to send infrared signals to the AC, an I2C LCD to display data locally, and the Blynk IoT platform for remote monitoring. Test results show that the SHT31 sensor has higher accuracy with an average error of 2.16°C compared to the DHT22 sensor with an average error of 3.36°C. The system successfully monitors room temperature in real-time and controls the AC through the Blynk application, and can serve as a foundation for the development of a fully automatic temperature-based AC control system.